Times of freedom. Peru’s hard republican learning after the Independence (Revista revoluciones, 2021)
The transition to the Republic, once independence was achieved in Peru, was far from becoming a bourgeois democratic regime, due to the fact that the survival of the social relations and values of colonial Peru were an obstacle for this purpose. For this reason, learning to live in a republican system was a difficult apprenticeship, since the being and consciousness of the vice-royal yesterday was still in force in our midst. In this way, the nascent State reproduced the formalities of a modern State, which wielded a double discourse; on the one hand, it embraced the ideals of a nativist preaching and, on the other, it rejected the real integration of the non-white masses into political life.
Keywords: Republic; modern state; citizenship; freedom; Nation